2018
DOI: 10.1016/j.molcel.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

α-Proteobacterial RNA Degradosomes Assemble Liquid-Liquid Phase-Separated RNP Bodies

Abstract: Ribonucleoprotein (RNP) granules play an important role in organizing eukaryotic mRNA metabolism via liquid-liquid phase separation (LLPS) of mRNA decay factors into membrane-less organelles in the cytoplasm. Here we show that the bacterium Caulobacter crescentus Ribonuclease (RNase) E assembles RNP LLPS condensates that we term bacterial RNP-bodies (BR-bodies), similar to eukaryotic P-bodies and stress granules. RNase E requires RNA to assemble a BR-body, and disassembly requires RNA cleavage, suggesting BR-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
211
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(220 citation statements)
references
References 54 publications
8
211
1
Order By: Relevance
“…Given the universal need for sensing in biology, we expect sensory phase separation to be exploited widely. Although our case studies are eukaryotic, a few examples of phase separation in bacteria have been reported recently (82,83). The field is wide open and filled with opportunities to discover more examples of sensory phase separation in different cell types and in different contexts, to dissect out the underlying molecular mechanism of sensory phase separation, to investigate how multiple sensory inputs are simultaneously integrated or processed separately, and to illuminate the costs and benefits of these molecular sensory strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the universal need for sensing in biology, we expect sensory phase separation to be exploited widely. Although our case studies are eukaryotic, a few examples of phase separation in bacteria have been reported recently (82,83). The field is wide open and filled with opportunities to discover more examples of sensory phase separation in different cell types and in different contexts, to dissect out the underlying molecular mechanism of sensory phase separation, to investigate how multiple sensory inputs are simultaneously integrated or processed separately, and to illuminate the costs and benefits of these molecular sensory strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Caulobacter crescentus (Ccr) Ribonuclease E (Ccr-RNase E) was the first bacterial protein identified that forms LLPS condensates both in vivo and in vitro termed BR-bodies (Al-Husini et al, 2018). BR-bodies are composed of Ccr-RNase E (the major bacterial mRNA decay nuclease), RNA degradosome components, and RNAs (Al-Husini et al, 2018). The intrinsically disordered C-terminal domain (CTD) of Ccr-RNase E, which is composed of alternating blocks of positive and negative charges, is both necessary and sufficient for the assembly of BR-bodies (Al-Husini et al, 2018).…”
Section: The Emergence Of Biomolecular Condensates In Organizing Thmentioning
confidence: 99%
“…The RNA degradosome which assembles with a suite of RNA decay related proteins which associated predominantly with the CTD is also shown with red ovals as degradosome proteins. (b) Ccr-RNase E phase separates in vitro (Al-Husini et al, 2018), forming a biomolecular condensate. (c) Subcellular localization of BR-bodies in C. crescentus and Escherichia coli.…”
Section: Similarities Between Br-bodies and Eukaryotic P-bodies Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario would explain the inability of T7 phage, which heavily relies on host bacterial resources, to replicate in N-24 Δhfq bacteria where the Hfq foci cannot form. Indeed, the formation of liquid-liquid phase separated structures akin to P bodies is not unprecedented in bacteria as the RNA degradation enzyme RNaseE of Caulobacter crescentus has been previously shown to form multiple liquid-liquid phase separated foci in response to diverse stresses to manage RNA turnover and disassemble when the stress that lead to their formation becomes alleviated 40 .…”
Section: Discussionmentioning
confidence: 99%